Gerakan Mahasiswa Pada Masa Orde Baru 1974-1978 :Dari Malari sampai NKK/BKK - Rahayu Hardita Dwi Widyanti; Yusuf Budi Prasetya; Irfan Ahmad Fauzi (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
The study of the dynamics of the student movement during the New Order era is an interesting topic for further research. The dynamic student movement constantly clashes with the structure of society which is often rigid and binding. Clashes between the student movement and the government also occurred during the New Order era. As one of the elements that contributed to the birth of the New Order, the relationship between the student movement and the New Order government actually appeared to be not harmonious. The student movement, which was considered suspended after the disbandment of KAMI in 1969, actually became increasingly heated in the mid-1970s. heated actions held by students led to the enactment of the NKK/BKK policy in 1978. Using historical methods, this research does not only use contemporary newspapers as one of its primary sources, but also the results of interviews with historical actors who were student activists in 1974 -1978.